Uma leitura epistêmica da teoria da identidade pessoal de John Locke e sua relação com a memória no capítulo 27 do livro 2 do Ensaio sobre o entendimento humano - Santos, Susie Kovalczyk dos (2022)
The traditional interpretation of John Locke's theory of personal identity says that he has a metaphysical thesis about personal identity whose criterion is episodic memory. In this paper, I contest this traditional interpretation and argue that Locke's interest focuses on the epistemic problem of personal identity. This alternative reading provides tools for dealing with the objections that are raised against Locke's theory. I will present the metaphysical interpretation of Locke's theory of personal identity and its main objections, that of circularity, of violation of the transitivity of identity, and of exigency. I will also present and challenge Strawson's reading that the scope of personal identity at a time encompasses the experiences that fall under the sphere of a person's moral, legal, and affective accountability at that time. However, Strawson's interpretation fails to recognize that Locke employs conscience and consciousness with different senses, and therefore ends up considering as a basis what is actually a consequence of the process of identification. I will explain why Locke is not doing metaphysics, but epistemology, in the chapter on identity through four arguments, that of the epistemic endeavor, that of the parallelism of idea formation and evidence discovery, that of words naming ideas in the mind, and that of the difference between real and nominal essence. In addition, I will present Locke's epistemic project in the work at hand, exploring his theories of ideas, knowledge, and memory. The idea that one is a person is formed through conscious experience, and we have intuitive knowledge of ourselves in the present. The possibility of consciousness turning to past experiences, taking the form of memory, and to possible future experiences, taking the form of prospection, provides evidence in the present of our own continued existence. Our knowledge about being the same self in the past is intuitive, when we have first-person memories, and demonstrative, when we have a chain of ideas that lets us know that we are the same. We can have sensory and demonstrative knowledge of the diachronic identity of other people. Different degrees of knowledge and certainty are involved in knowing about one's own identity and the identity of others, and that these differences lie behind Locke's demarcation between the idea of the identity of persons and that of human beings is not a difference between two types of entities, but two different ways of knowing. Finally, this version of the Lockean theory of personal identity deals with the objections of circularity, violation of the principle of identity transitivity, and exigency. In addition, I explore the implications of memory being an epistemic criterion of personal identity for accountability and respond to two possible objections to the epistemic theory of personal identity. Although this work focuses on Lockean theory, I intend that the ideas proposed here can be useful for contemporary discussions of possible relations between memory and personal identity.